Environmental Cost Disclosure and Financial Performance of Listed Oil and Gas Firms in Nigeria - Clifford Obiyo Ofurum; Iwunna, Stella Adaremmy; Nmehielle, Collins O. (Research Parks Publishers, 2022)
The study investigated environmental cost disclosure and financial performance of oil and gas companies listed on NSE for the period of 2008 to 20019. The study specifically examined the impact of environmental cost disclosure, which includes waste management costs and pollution control costs, using return on assets as proxy of financial performance. The study adopted the ex-post facto research design and the data was sourced from the companies’ annual audited financial reports and Department of Petroleum Resources (DPR) for the period from 2008 to 2019. The panel data regression technique was applied in estimating the study’s parameters. Findings showed that employee health and safety costs have a negative and significant relationship with return on assets of oil and gas companies in Nigeria and also no significant relationship with return on equity. The study therefore concluded that environmental cost disclosure has a significant but mixed effect on the financial performance of oil and gas companies listed on the NSE for the period.